2007
DOI: 10.1002/pssb.200675142
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity of Ga doped polycrystalline ZnO films grown by reactive plasma deposition

Abstract: Photoconductivity and photo-absorption of polycrystalline Ga-doped ZnO (GZO) thin films with film thickness of 200 nm have evaluated compared with undoped ZnO films. The GZO and undoped ZnO thin films were deposited on alkali-free glass substrate at 200 °C by a reactive plasma deposition with DC arc discharge technique under an oxygen gas flow rate from 0 to 30 sccm. Undoped ZnO films with carrier concentration of 2.50 × 10 18 and 7.96 × 10 18 cm -3 have exciton absorption at about 3.28 eV. For these films, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…This is consistent with our results that the values of drift mobility for electrons were larger than that of holes. However, the values obtained here seem to be somewhat small, compared with the values of Hall mobility [15]. When carriers are trapped and released by shallow levels, value of drift mobility becomes small, while value of Hall mobility does not.…”
contrasting
confidence: 57%
“…This is consistent with our results that the values of drift mobility for electrons were larger than that of holes. However, the values obtained here seem to be somewhat small, compared with the values of Hall mobility [15]. When carriers are trapped and released by shallow levels, value of drift mobility becomes small, while value of Hall mobility does not.…”
contrasting
confidence: 57%
“…While synthesizing TCO thin films, it is a common practice to introduce impurities such as In, Al, Ga, N, P, As and F [5], within ZnO thin films in order to enhance the optoelectronic properties. ZnO : Ga (GZO) thin films have been deposited by several techniques such as molecular beam epitaxy [6], pulsed laser deposition [7], sintering [8], chemical spray [9,10], rf magnetron sputtering [11], ion plating [12] and solid state reaction [13]. Photoluminescence (PL) and 3 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…All these changes improved transparency in the visible range, indicating that some structural reformation had occurred. Kishimoto et al 13) also reported higher transmittance in the visible wavelength for films having higher carrier concentration. Another noticeable feature can be seen at shorter wavelengths where band-toband optical transition can be excited.…”
mentioning
confidence: 92%